Knowledge and practice of hemodialysis catheter care and associated factors among patients on maintenance hemodialysis: An analytical cross-sectional study - Maheda Jilisha Lucas; Emmanuel Sumari; Joel Seme Ambikile (PLoS ONE, 2026)
Background Effective care of hemodialysis catheters (HDCs) is essential for preventing complications, particularly catheter-related infections, among patients receiving maintenance hemodialysis. However, gaps in patient knowledge and practice may compromise optimal catheter care. This study assessed the level of knowledge and practice of HDC care and identified factors associated with these outcomes among patients on maintenance hemodialysis. Methods A cross-sectional study was conducted among 97 patients undergoing maintenance hemodialysis. Data were collected using a structured questionnaire assessing socio-demographic and clinical characteristics, as well as knowledge and practice related to HDC care. Knowledge and practice scores were categorized using an 80% cutoff. Bivariate and multivariable logistic regression analyses were performed to identify factors associated with knowledge and practice. Model fitness and multicollinearity were assessed. Results Overall, 51.5% of respondents demonstrated satisfactory knowledge, while 45.4% reported satisfactory HDC care practices. Knowledge was highest regarding the purpose and insertion site of the catheter but lower for aspects related to infection recognition and dressing care. In multivariable analysis, female sex (AOR: 3.09; 95%CI: 1.12, 8.54; p = 0.030) and shorter duration on hemodialysis (<2 years) (AOR: 3.66; 95%CI: 1.28, 10.50; p = 0.016) were independently associated with satisfactory knowledge. Regarding practice, knowledge emerged as the only independent predictor, with respondents having satisfactory knowledge demonstrating significantly higher odds of satisfactory practice (AOR: 47.39; 95%CI: 11.14, 201.64; p < 0.001). Other variables were not significantly associated with practice after adjustment. Conclusion Less than half of patients demonstrated satisfactory HDC care practices despite moderate levels of knowledge. Knowledge was strongly associated with practice, highlighting its potential importance in supporting optimal catheter care behaviors. These findings indicate that targeted and sustained patient education may be important in improving knowledge and supporting better catheter care practices. Further multicenter and longitudinal studies using more robust measurement approaches are recommended to better clarify factors influencing HDC care practices and related outcomes.